Training Centre dan Jasa Ketekniksipilan Universitas Negeri Makassar - Taufiq Natsir (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
As an effort to develop an entrepreneurial culture atthe Makassar State University (UNM vision), it is necessary toencourage and improve Laboratory empowerment in theDepartment of Civil Engineering and Faculty of EngineeringPlanning. The existence of equipment in this laboratory,workshop and drawing studio, if empowered is believed to beable to provide large income and with the PPUPIK programfrom the Higher Education by trying to provide training andoffering services in the form of TraininngCenters and Servicesin the field of discipline in an organized manner not onlyproviding income / large income but also can train skills /skills and also develop an entrepreneurial spirit for students. hemethods used to achieve the above objectives are: 1) Conductbusiness promotion through advertisements (newspapers,radio, websites, pamphlets, banners, benner, brochures); 2)establish cooperation and partnerships (service/agencies/institutions/companies, schools/colleges/tutoring, associations/individuals) both government and private.